Issues and Challenges in Online Teaching and Learning during Movement Control Order (MCO) - Shaharudin, Ismail; Halimaton Sa'adiah, Ariffin; Zul Hilmi, Abdullah (INTI International University, 2020)
COVID-19 is an infectious disease caused by a newly discovered strain of coronavirus; a type of virus known to cause respiratory infections in humans. This new strain was unknown before December 2019. The first case of COVID-19 in Malaysia was detected on 24 January 2020. The Movement Control Order, commonly referred to as the MCO, has been announced by The Prime Minister on 16 March 2020. As the results, many non-essential sectors including higher education institutional (HEI) in Malaysia are close. The teaching and learning processes need to implement in a new norm – Online Teaching and Learning. Lecturers and students experience a new way of teaching and learning processes. This paper discusses issues and challenges faced by lecturers and students on Teaching and Learning process via Online Teaching and Learning mode during the Malaysia Movement Control Order (MCO).